The performance structure in women's pole vault - Ionescu, M.
The pole vault is based on the kinetic energy developed by the approach, combined with the force of the plant that give a pendulum movement to the human body on the pole. The movement continues with the body pull and lift over the pole grip. The phases of pole vault would be: approach, plant, take off, work on the pole (long and short pendulum movement, pole release) and bar clearance. There are some differences because of straight and body structure between women and men vaulters.